Comparative Analysis of Reactivity Calculations for the CERMET Fueled ADS with Serpent and MCNP6 Codes - Thanh Mai, Vu; Hartanto, Donny; Nhu Viet Ha, Pham; Thi Dung, Nguyen; Thi Hoa, Bui; Ho Phong, Vi (VNU Journal of Science: Mathematics - Physics, 2021)
The ADS (accelerator driven system) is recognized as a promising system to annihilate the radioactivity of nuclear waste with its inherent safety feature and waste transmutation potential. Thus, conceptual designs of ADS are widely carrying out. In order to verify the accuracy of an innovative ADS core modeling by using simulation codes, the reactivity calculations of CERMET fueled ADS were conducted using two Monte Carlo codes, Serpent and MCNP6 with ENDF/B-VII.0 library. The comparison shows a good agreement between two codes including the eigenvalue (less than 50 pcm) and fuel temperature feedback (discrepancy is within the standard deviation). It implies that the ADS was modelled successfully and can be used for further investigation.   Keywords: CERMET fueled ADS, Serpent code, MCNP6, reactivity calculation.